Pendataan Sarpras (Sarana Prasarana) Berbasis PHPrad SMK Negeri 2 Teknologi dan Rekayasa Nabire Provinsi Papua Tengah - Ester Ayuk Pusvita; Lailil Mahmudah (STMIK Pesat Nabire, 2024)
Effective and efficient management of facilities and infrastructure (sarpras) is crucial for supporting educational operations at SMK Negeri 2 Teknologi dan Rekayasa Nabire, Central Papua Province. To enhance sarpras management, this research proposes the implementation of a PHP-RAD (Rapid Application Development) based data management system. The system is designed to simplify the processes of registration, maintenance, and reporting of sarpras by leveraging web-based technology that allows for flexible access. The research methodology includes needs analysis, system design, application development using PHP and MySQL, as well as implementation and evaluation. The system features modules such as sarpras registration, data management, condition reporting, and real-time information search and update capabilities. The expected outcome of this system development is increased efficiency in sarpras management, with more accurate and up-to-date data. The system is anticipated to improve decision-making processes and planning for sarpras development at SMK Negeri 2 Teknologi dan Rekayasa Nabire.